GRAMMATICAL ERROR ANALYSIS ON STUDENTS’ ARGUMENTATIVE ESSAY WRITING - Saputri, Nur Kholiza Eka; Ilma, Ridha; Dalilan, Dalilan (Universitas Muhammadiyah Palembang, 2023)
This research aimed at finding out: (1) the type of grammatical error by using categories of surface strategy taxonomy written by the fifth semester students in their academic essays; and (2) the most frequent type of grammatical error by using categories of surface strategy taxonomy written by the fifth semester students in their academic essays at one of state universities in Palembang. The method of this research was a descriptive quantitative method. The data were collected from 34 essays that were written by the students. The researchers used students’ writing sheets as the instrument. In this case, all types of grammatical errors were classified and described based on the taxonomy of grammatical errors regarding omission, addition, misformation, and misordering. In analyzing students’ errors, the procedure of error analysis was applied. They were identification, description, and explanation. Based on the result of the analysis, there were 257 grammatical errors found in the students’ argumentative essay. It was found that the students made 110 (42.80%) errors of omission, 72 (28.01%) errors of addition, 70 (27.23%) errors of misformation, and 5 errors (1.94%) of misordering. Thus, it can be concluded that omission error was the highest, while error in misordering was the lowest.